Formulation of a kit under Good Manufacturing Practices (GMP) for preparing [111In]In-BnDTPA-trastuzumab-NLS injection: a theranostic agent for imaging and Meitner-Auger Electron (MAE) radioimmunotherapy of HER2-positive breast cancer - Conrad Chan; Vanessa Prozzo; Sadaf Aghevlian; Raymond M. Reilly (SpringerOpen, 2022)
Abstract Background 111In[In]-BnDTPA-trastuzumab-NLS is a radiopharmaceutical with theranostic applications for imaging and Meitner-Auger electron (MAE) radioimmunotherapy (RIT) of HER2-positive breast cancer (BC). Nuclear localization sequence (NLS) peptides route the radiopharmaceutical to the nucleus of HER2-positive BC cells following receptor-mediated internalization for RIT with subcellular range MAEs. The γ-photons emitted by 111In permit tumour imaging by SPECT. Our aim was to formulate a kit under Good Manufacturing Practices conditions to prepare 111In[In]-BnDTPA-trastuzumab-NLS injection for a first-in-human clinical trial. Results Trastuzumab was derivatized with p-SCN-BnDTPA to introduce Bn-DTPA for complexing 111In, then modified with maleimide groups for conjugation to the thiol on cysteine in NLS peptides [CGYGPKKKRKVGG]. BnDTPA-trastuzumab-NLS (5 mg in 1.0 mL of 0.05 M ammonium acetate buffer, pH 5.5) was dispensed into unit dose sterile glass vials to produce kits for labeling with 100-165 MBq of 111In[In]Cl3. The kits met specifications for protein concentration (4.5-5.5 mg/mL), volume (0.95-1.05 mL), pH (5.5-6.0), appearance (clear, pale-yellow, particulate-free), BnDTPA substitution level (2.0-7.0 BnDTPA/trastuzumab), purity and homogeneity (SDS-PAGE and SE-HPLC), 111In labeling efficiency (> 90%), binding to HER2-positive SK-BR-3 human breast cancer cells (Ka = 1-8 × 108 L/mmol; Bmax = 0.5-2 × 106 sites/cell), NLS peptide conjugation (upward band shift on SDS-PAGE), sterility (USP Sterility Test) and endotoxins (USP Bacterial Endotoxins Test). 111In-BnDTPA-trastuzumab-NLS injection met specifications for pH (5.5-6.5), radiochemical purity (≥ 90%), radionuclide purity (≥ 99%), appearance (clear, colourless, particle-free) and sterility (retrospective USP Sterility Test). Kits were stable stored at 2-8 °C for up to 661 days (d) meeting all key specifications. Protein concentration remained within or just slightly greater than the specification for up to 139 d. 111In[In]-BnDTPA-trastuzumab-NLS injection was stable for up to 24 h. An expiry of 180 d was assigned for the kits and 8 h for the final radiopharmaceutical. Conclusion A kit was formulated under GMP conditions for preparing 111In[In]-BnDTPA-trastuzumab-NLS injection. This radiopharmaceutical was safely administered to 4 patients with HER2-positive BC to trace the uptake of trastuzumab into brain metastases before and after MRI-guided focused ultrasound (MRIg-FUS) by SPECT imaging.